Insecticidal properties of capsaicinoids and glucosinolates extracted from Capsicum chinense and Tropaeolum tuberosum - Claros Cuadrado, José L. (2019)
Food security and biodiversity conservation are threatened by the emergence and spread of pest and pathogens, and thus there is a current need to develop pest management strategies that are sustainable and friendly to the environment and human health. Here, we performed laboratory and field bioassays to evaluate the insecticidal effects of several concentrations of capsaicinoids and glucosinolates (separately and mixed) on an aphid pest (Aphis cytisorum). The capsaicinoids were extracted from the fruits of Capsicum chinense and glucosinolates from the tubers of native Andean crop Tropaeolum tuberosum. We found that both capsaicinoids and glucosinolates have a biocidal effect on A. cytisorum, acting within a fairly short time. Under laboratory conditions, the toxicity of the compounds increased in relation to their concentrations, causing a high percentage of mortality (83–99%) when the aphids were exposed to dilutions of 10% capsaicinoids, 75–100% glucosinolates, or a mixture of 10% capsaicinoids and 90% glucosinolates. The mortality of aphids sprayed in the field with 5% capsaicinoids, 50% glucosinolates, or with a mixture of 5% capsaicinoids and 45% glucosinolates reached 87–97%. Results obtained from laboratory and field experiments were consistent. Our results suggest the potential use of bioinsecticides based on capsaicinoids and/or glucosinolates as an effective alternative to synthetic pesticides.